2017
DOI: 10.1016/j.wem.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Use in Prehospital Uncontrolled Hemorrhage

Abstract: The use of tranexamic acid (TXA) in the treatment of trauma patients was relatively unexplored until the landmark Clinical Randomisation of an Antifibrinolytic in Significant Haemorrhage-2 (CRASH-2) trial in 2010 demonstrated a reduction in mortality with the use of TXA. Although this trial was a randomized, double-blinded, placebo-controlled study incorporating > 20,000 patients, numerous limitations and weaknesses have been described. As a result, additional studies have followed, delineating the potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Meanwhile, goal directed therapy represents the current standard (128,129). Along with these changes, the use of additional medication such as Tranexamic acid (TXA) have been shown to be important in acute hemorrhage conditions; some suggest an enhancement of clot formation (130), a group of patients presenting with depletion of fibrinolysis treated with TXA to develop a significantly improved fibrin clot strength (117,(131)(132)(133)(134)(135).…”
Section: Published Guidelinesmentioning
confidence: 99%
“…Meanwhile, goal directed therapy represents the current standard (128,129). Along with these changes, the use of additional medication such as Tranexamic acid (TXA) have been shown to be important in acute hemorrhage conditions; some suggest an enhancement of clot formation (130), a group of patients presenting with depletion of fibrinolysis treated with TXA to develop a significantly improved fibrin clot strength (117,(131)(132)(133)(134)(135).…”
Section: Published Guidelinesmentioning
confidence: 99%
“…Antifibrinolytics Coagulopathy increases mortality in severe exsanguination. Haemorrhagic death [79][80][81][82][83][84] and multi-organ failure with severe shock [85] decrease with administration of tranexamic acid TXA) within 3 h after trauma, without increasing the risk of thrombosis [79]. The dose is 1 g intravenously (IV) over 10 min, followed by 1 g IVover 8 h [61].…”
Section: Pharmacologic Methodsmentioning
confidence: 99%
“…Prehospital administration of TXA during aeromedical transport was found to increase the risk of venous thromboembolic events compared with administration at the emergency department [111]. It has been recommended that a one-gram prehospital TXA bolus be administered in high-risk patients followed by subsequent doses guided by thromboelastography [42]. Additionally, a pharmacovigilance study concluded that there was no increased risk of thromboembolic events in FC-treated patients [219].…”
Section: Safetymentioning
confidence: 99%